New documents on the arrest of family of General N. N. Stogov in 1919 - A. V. Ganin (Омский научный вестник: Серия "Общество. История. Современность")
The publication touches upon the issue of political and social embedding in the conditions of Soviet Russia of representatives of the former generals and the General Staff of the Russian Imperial Army and members of their families, which is relevant in modern Russian historiography. In order to expand ideas on the designated topic, this paper for the first time introduces into scientific circulation the materials of the archival and investigative case against the family members of the head of the white underground in Moscow, General N. N. Stogov. The study, which is theoretically based on a biographical method, sheds light on the features of the repressive practice of the Cheka during the Civil War and on the history of the confrontation between the Chekists and the white underground in Moscow. The work is addressed to researchers of the events of the Revolution and the Civil War in Russia, military, social and political history.